Realism and Imagination in Child Foreign-Language Productions: Three Reasons for an Early Exit from the 'Gold Standard' of Personal Experience. Issue 3 (1st September 2016) - Hong, Seongeun; Kellogg, David
Abstract: Teachers often assume that personal experience is a rich resource for classroom chat and a gold standard for meaningful exchange of information. But in this paper, we first present three kinds of reasons for suspecting that primary intersubjectivity—the 'me and you' relationship in which personal experiences are directly exchanged between interlocutors—may be highly circumscribed in affordances for second or foreign language learners and, in contrast, secondary intersubjectivity—with more third-person reference and more imagined experiences—may offer higher levels of grammatical creativity. Firstly, and most theoretically, Vygotsky's work on the development of imagination suggests that one of the more important steps is freeing word meanings from recalled perceptual experience. Secondly, research from both teaching young learners a second language and from first language acquisition confirms that one way this happens is that interactions based on primary intersubjectivity give way to those based on secondary intersubjectivity, where children develop joint attention to some object or person external to the dyad. Thirdly, we present some data from Korean elementary school classrooms showing that children are markedly more 'constructive'—that is, much freer from the influence of fixed expressions—when they are talking about textbook characters than when they are talking about themselves.